PENDAMPINGAN IMPLEMENTASI LESSON STUDY PADA GURU MGMP BAHASA INDONESIA SEBAGAI UPAYA PENINGKATAN KUALITAS PEMBELAJARAN JARAK JAUH - Efendi; Syamsuddin; Asrianti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The problems that occurred during the Covid-19 pandemic in the world of education had an impact on the quality of learning. Teachers and students adapt to distance learning which results in the need for a deep comprehensive understanding of effective learning techniques during a pandemic. The collaboration system and understanding of technological literacy are things that can be done to improve the quality of the distance learning process through increasing teachers' understanding of the determination of Lesson Study. This service activity will be held in Blended (online and offline) using socialization and mentoring methods. The implementation of Lesson Study training activities is carried out offline while mentoring and implementation is carried out online. distance learning and (3) giving the teacher real experience in the classroom in developing teaching materials and distance learning according to the needs of students. The results of the service activities show an increase in models and the development of teaching materials in the form of modules in peer teaching to conduct open classes and teachers can make lesson plans according to the scenario collaboratively with cognate maple teachers